2014
DOI: 10.3390/ijerph110808347
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure of Nigerians to Mutagens and Estrogen-Like Chemicals

Abstract: Food and drinking water are poorly delineated sources of human exposure to chemical food mutagens and endocrine-disrupting chemicals. In this study, we investigated the presence of mutagens and chemicals exhibiting estrogenic activity in the daily diet of Nigerians, using in vitro assays. Commercially processed foods or snacks and various brands of pure water sachets were extracted by solid-phase extraction and liquid-liquid extraction, respectively. Mutagenicity was determined by the conventional Ames test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, in their material the highest estrogenic activities were recorded for waters packaged in either non-reusable poly(ethylene terephthalate) or reusable glass bottles, and even water packed in Tetra Pak™ bricks contained high levels (14–44 ng/L). More recently, five sachet-packed drinking water samples (a third of the samples analyzed) from Nigeria were reported to be estrogenic, with estradiol equivalents ranging from 0.79 to 44.0 ng/L [29], further reinforcing the contention that exposure to EDCs via drinking water can be of concern in some parts of the world. Interestingly, in the present study estrogenic activity was neither found in any brand of bottled still or mineral water, nor in tap water, testifying to a high chemical quality of these products in Finland.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in their material the highest estrogenic activities were recorded for waters packaged in either non-reusable poly(ethylene terephthalate) or reusable glass bottles, and even water packed in Tetra Pak™ bricks contained high levels (14–44 ng/L). More recently, five sachet-packed drinking water samples (a third of the samples analyzed) from Nigeria were reported to be estrogenic, with estradiol equivalents ranging from 0.79 to 44.0 ng/L [29], further reinforcing the contention that exposure to EDCs via drinking water can be of concern in some parts of the world. Interestingly, in the present study estrogenic activity was neither found in any brand of bottled still or mineral water, nor in tap water, testifying to a high chemical quality of these products in Finland.…”
Section: Resultsmentioning
confidence: 99%
“…This can occur during the manufacturing process, transportation, storage, or even during the cooking process. In addition, BPA can also be released into the environment and contaminate soil and water sources, leading to potential exposure through food [26,27]. Studies have shown that BPA is present in a wide range of food products, including canned foods and even culinary aromatic herbs and spices.…”
Section: Watermentioning
confidence: 99%
“…The potential health effects of BPA in food are a concern because BPA is an endocrine disruptor. BPA can mimic the effects of estrogen in the body, leading to potential hormonal imbalances and other health problems [26][27][28][29][30][31][32][33][34]. Exposure to BPA has been linked to a range of health problems, including reproductive disorders, developmental delays, and cancer [35].…”
Section: Watermentioning
confidence: 99%
“…Fascinatingly, water packaging into polyethylene sachets (as a form of water vending) has assumed an innovative status which has spread from its origin in Nigeria to other West African countries (Omole et al, 2015). Most studies on the safety of this sachet-packed and bottled water samples revealed them to be contaminated with pathogenic bacteria and coliform (Edema et al, 2011), heavy metals (Edema et al, 2011) and estrogens (Ignatius et al, 2010;Omoruyi et al, 2014). Despite the growing dependence on sachet-packed and bottled water, the majority of Nigerians still rely on ground water as their major source of drinking water.…”
Section: Drinking Water Quality In Nigeria: Pre-sustainable Developmementioning
confidence: 99%